Diverse origins of Arctic and Subarctic methane point source emissions identified with multiply-substituted isotopologues. (1st September 2016) - Douglas, P.M.J.; Stolper, D.A.; Smith, D.A.; Walter Anthony, K.M.; Paull, C.K.; Dallimore, S.; Wik, M.; Crill, P.M.; Winterdahl, M.; Eiler, J.M.; Sessions, A.L.
Abstract: Methane is a potent greenhouse gas, and there are concerns that its natural emissions from the Arctic could act as a substantial positive feedback to anthropogenic global warming. Determining the sources of methane emissions and the biogeochemical processes controlling them is important for understanding present and future Arctic contributions to atmospheric methane budgets. Here we apply measurements of multiply-substituted isotopologues, or clumped isotopes, of methane as a new tool to identify the origins of ebullitive fluxes in Alaska, Sweden and the Arctic Ocean. When methane forms in isotopic equilibrium, clumped isotope measurements indicate the formation temperature. In some microbial methane, however, non-equilibrium isotope effects, probably related to the kinetics of methanogenesis, lead to low clumped isotope values. We identify four categories of emissions in the studied samples: thermogenic methane, deep subsurface or marine microbial methane formed in isotopic equilibrium, freshwater microbial methane with non-equilibrium clumped isotope values, and mixtures of deep and shallow methane (i.e., combinations of the first three end members). Mixing between deep and shallow methane sources produces a non-linear variation in clumped isotope values with mixing proportion that provides new constraints for the formation environment of the mixing end-members. Analyses of microbial methane emitted from lakes, as well as a methanol-consuming methanogen pure culture, support the hypothesis that non-equilibrium clumped isotope values are controlled, in part, by kinetic isotope effects induced during enzymatic reactions involved in methanogenesis. Our results indicate that these kinetic isotope effects vary widely in microbial methane produced in Arctic lake sediments, with non-equilibrium Δ18 values spanning a range of more than 5‰.